THE ENHANCEMENT OF MATHEMATICAL PROBLEM SOLVING ABILITY OF SENIOR HIGH SCHOOL STUDENTS THROUGH QUANTUM LEARNING - Julita Julita (Jurnal Infinity, 2017)
This study is aimed to examine the quality of quantum learning imfluence toward the enhancement of mathematical problem solving ability of Senior High School students, both viewed entirely and based on mathematical initial ability (MIA) category.  In particular, this study is aimed to examine enhancement difference of students’ mathematical problem solving ability in a whole and in each level of mathematical initial ability (high, medium and low) between students who receive quantum learning and students who receive conventional learning. This study use experimental quasi with pretests-posttest control group design.  Population of this study are Senior High School students in Bogor City. Data is obtained through problem solving ability test and mathematical initial ability data. The result of study showed that students who receive quantum learning have enhancement of mathematical problem solving ability which is higher than students who receive conventional learning. There is no difference enhancement of mathematical problem solving ability both entirely and in each level of mathematical initial ability, except for students with high level of initial mathematical ability